2017
DOI: 10.3390/molecules22050756
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Carboxymethyl Pachyman in Fluorouracil-Treated CT26-Bearing Mice

Abstract: 5-Fluorouracil (5-FU) is the chemotherapeutic agent of first choice for the treatment ofcolorectal cancer, however, treatment-related liver toxicity remains a major concern. Thereby, it is desirable to search for novel therapeutic approaches that can effectively enhance curative effects and reduce the toxic side effects of 5-FU. Carboxymethyl Pachyman (CMP) exhibits strong antitumor properties, but the antitumor and hepatoprotective effects of CMP and the molecular mechanisms behind these activities, are howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…5-FU-induced organ toxicity is accompanied by a marked reduction in Nrf-2 along with an increase in Keap-1. Hence, studies showed that activation of Nrf-2 could be beneficial in the protection against 5-FU-induced organ injury [35,36]. Similarly, data in the present study indicated that 5-FU induced a significant decrease in renal tissue expression of Nrf-2 protein compared to both normal and AuNPs control groups.…”
Section: Aunps Treatment Corrected 5-fu-induced Imbalance Of Nrf-2/keap-1 Axis In Renal Tissuessupporting
confidence: 78%
“…5-FU-induced organ toxicity is accompanied by a marked reduction in Nrf-2 along with an increase in Keap-1. Hence, studies showed that activation of Nrf-2 could be beneficial in the protection against 5-FU-induced organ injury [35,36]. Similarly, data in the present study indicated that 5-FU induced a significant decrease in renal tissue expression of Nrf-2 protein compared to both normal and AuNPs control groups.…”
Section: Aunps Treatment Corrected 5-fu-induced Imbalance Of Nrf-2/keap-1 Axis In Renal Tissuessupporting
confidence: 78%
“…In consistent, Chai et al reported that CMP has no adverse effects on mice as well. Wang et al showed that CMP could enhance the tumour inhibition rate of 5‐FU and decrease the liver injuries simultaneously caused by 5‐FU in CT26 tumour‐bearing mice …”
Section: Toxicitymentioning
confidence: 99%
“…GA significantly inhibited tumor growth in CT26 cell xenograft-bearing BALB/c mice, similar to 5-fluorouracil (5-FU) [ 33 ]. However, 5-FU, which is an effective and commonly used anticancer agent for the treatment of colon cancer, has side effects that may cause damage to the liver and immunological function [ 34 , 35 ]. In our study, GA exhibited excellent anticancer activity in vivo without causing injury to the major organs or hepatorenal dysfunction; thus, GA might be a safe and effective anticancer chemotherapeutic agent for CRC treatment.…”
Section: Discussionmentioning
confidence: 99%